Pemanfaatan Bunga Telang Menjadi Produk Olahan Sebagai Peluang Usaha Masyarakat Desa Gedubang Jawa - Ade Fadillah FW Pospos; Riyandi Saputra (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
Aims of this activity is to create products from processed butterfly pea flowers as a business opportunity. This community service activity is conducted by the students of KKN IAIN Langsa. The method applied in the community service program in Geudeubang Jawa Village, Langsa City involves active participation from the PKK mothers, local residents, and local village officials. This socialization activity adopts an approach through lectures, demonstrations, and interactive discussions with participants, also allowing them to try making processed products from butterfly pea flowers themselves. The outcome of this activity is that participants are able to create fresh drinks and jam from butterfly pea flowers. The participants showed great enthusiasm in participating in the activity. Furthermore, the activity increased their knowledge about the benefits of butterfly pea flowers and also provided them with new business opportunities to pursue.